The Legal Implications of Indonesian Positive Law On The Rights and Obligations of Husband and Wife in Mixed Marriage - Muh. Raihan Muflih Anhar (Universitas Negeri Gorontalo, 2026)
Marriage is a legal event that establishes a physical and spiritual bond between husband and wife with the aim of creating a harmonious family. Law Number 1 of 1974 affirms marriage as a union founded upon the belief in the Almighty God, thereby emphasizing that it is not only a social institution but also a religious one. This provision further underscores that the rights and obligations of husband and wife are a direct consequence of marriage. The regulation of spousal rights and obligations is stipulated in Articles 30–36 of Law Number 1 of 1974 and reaffirmed in the Compilation of Islamic Law. In the context of mixed marriage, specific provisions are found in Articles 57–62, which govern matters of citizenship and marital validity. However, the findings of this study indicate that there are no fundamental differences between the rights and obligations of spouses in ordinary marriages and those in mixed marriages. Consequently, couples entering into mixed marriages remain subject to Indonesian positive law, which guarantees equality of rights and obligations for both parties. Thus, national law functions to reinforce the balance of roles between husband and wife within the household, while simultaneously ensuring legal certainty for couples with different nationalities.